Relationship of species Piper based on morphological and leaf essential oils characters in Yogyakarta - PURNOMO PURNOMO; RANI ASMARAYANI (Biodiversitas Journal of Biological Diversity, 2005)
Some of Piper species were used for traditional medicines and condiments. The leaf essential oil (terpenoid) of those Piper species usually were used as a main component in traditional medicine. The taxonomycal study was aimed to determined Piper species relationships based on morphological and leaf essential oils characters. The plants were obtained by exploring this province, and samples were collected for identification and leaf essential oils isolation purposes. Species identification were carried out based on identification key (Backer and Bakhuizen v.d. Brink, 1965; Heyne, 1987; Shaorong, 1982). The isolation of leaf essential oils was carried out using Stahl destillation method, and their composition were interpreted with liquid gas chromatography, using caryophyllene and ï¡-pinene as a standard of essential oils component. Dendrogram, which showed phenetic relationships among those species, were obtained by hierarchical cluster analysis method. Results of the research showed that there were 8 species found as cultivated plants in Yogyakarta, which were P. miniatum Bl., P. betle L., P. recurvum Bl., P. aduncum L., P. nigrum L., P. cubeba L.f., P. retrofractum Vahl., and P. sarmentosum Roxb. Ex Hunter. Relationship between species of Piper based on morphological character showed that P. aduncum and P. sarmentosum at thesame cluster on 69.2% similarity level, and 40.4% similarity level to the other clusters. Relationsips between species of Piper based on leafessential oils character resulted the difference cluster among the species, P. retrofractum separated from the other species at 45.5% similarity level, P. aduncum and P. cubeba indicated the higest similarity level (81.5%).@ 2004 Jurusan Biologi FMIPA UNS SurakartaKey words: relationship, Piper, morphology, leaf essential oils, taxonomic characters.